Congenital Imprinting Diseases: Aetiology, Pre- and Perinatal Manifestations, Diagnosis and Care of Affected Families and Pregnancies - Eggermann, Thomas; Kagan, Karl Oliver; Dufke, Andreas (Geburtshilfe und Frauenheilkunde, 2025)
Congenital Imprinting Disorders (ImpDis) are caused by abnormal expression of parentally imprinted genes. They are characterized by disturbances of imprinting marks which are a specific type of epigenetic signatures and occur either sporadic or familial. So far, twelve ImpDis have been identified, eight of them manifest prenatally or in the neonate period. With exception of abdominal wall defects, ImpDis are rarely associated with major malformations, but predominant early manifestations are disturbed pre- and/or postnatal growth, muscular hypotonia, neonatal feeding difficulties and metabolic/hormonal dysfunction. With few exceptions prenatal clinical features of ImpDis are unspecific and manifest only in the late second or third trimester. In some ImpDis, behavioural, developmental, and neurological symptoms might emerge, and in single ImpDis there is a higher risk of cancer in childhood. Prenatal diagnosis plays a crucial role in appropriate pregnancy management and initial care of the newborn, which in turn has positive impact on the life-long outcome of the patient. Furthermore, the diagnosis of ImpDis is relevant for the prevention of pregnancy risks such as preeclampsia and possible reproductive problems in future pregnancies and other family members. Genetic analysis is not straightforward, and imprinting disturbances may escape both DNA sequencing analysis and (molecular-)cytogenetic diagnostics. After introducing the topic with a case report, this review focuses on the recognition of ImpDis including maternal and family history, exogeneous and genetic risk factors, fetal imaging, and genetic findings as well as interdisciplinary care and treatment approaches in the management and decision making of affected families and pregnancies.
Keywords: imprinting disorders; fetal imaging; genetic diagnosis; genetic counselling